1983
DOI: 10.1016/0014-5793(83)80745-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine modification in DNA by BcnI methylase yields N4‐methylcytosine

Abstract: and keywords not received

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…malvacearum (Tables 2 and 3), which possess at least one restriction endonuclease (30) In this study, we have found that m4C is frequently present in mesophilic bacteria as a minor genomic base, just as previously found in thermophilic bacteria (11) and' in the mesophile Bacillus centrosporus (19). m5C was not found in the DNA of any of 15 examined thermophiles which grow optimally at -60°C (11).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…malvacearum (Tables 2 and 3), which possess at least one restriction endonuclease (30) In this study, we have found that m4C is frequently present in mesophilic bacteria as a minor genomic base, just as previously found in thermophilic bacteria (11) and' in the mesophile Bacillus centrosporus (19). m5C was not found in the DNA of any of 15 examined thermophiles which grow optimally at -60°C (11).…”
Section: Resultssupporting
confidence: 75%
“…Janulaitis and co-workers (6,19,20) have demonstrated that site-specific DNA methylases from B. centrosporus, Micrococcus varians, and Citrobacter freundii catalyze the formation of m4C residues within sequences recognized by the restriction endonucleases of these cells. However, some cytosine methyltransferases might control DNA repair, expression, replication, or transposition like the adenine-specific dam methylase in E. coli (15,23,29,35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact raises the possibility that SuaI may generate 5mC at its recognition sites, which occur elsewhere in the S. acidocaldarius genome, and promote high rates of C-to-T transition at these sites. An alternative explanation is based on the observation that a number of R-M systems methylate the exocyclic N of cytosine to yield N 4 mC (14). This modified base occurs in the DNAs of both mesophiles and thermophiles (6) and thus does not seem to correlate strongly with high growth temperature.…”
mentioning
confidence: 99%
“…In general, two enzymes compose a restriction-modification system: an endonuclease or restriction enzyme that cleaves a specific DNA sequence and a methylase that modifies the same sequence by transferring methyl groups from Sadenosylmethionine to either adenine (N-6 position) or cytidine (C-5 or N-4 position [13]). Methylation blocks cleavage by the restriction enzyme and thereby prevents the destruction of cellular DNA.…”
mentioning
confidence: 99%